Forty-One Key Races
The article "Forty-One Key Races" previews major 1976 California contests for the U.S. Senate, House of Representatives, State Senate, and State Assembly, highlighting competitive districts and party registration advantages. It describes Senator John Tunney's difficult reelection bid against Republican S. I. Hayakawa and outlines several closely watched congressional races where party control could shift. In the State Senate, Democrats hope to expand their 25–15 majority but face long odds in achieving a two-thirds margin, with several open seats and potential breakthrough opportunities for women candidates. The State Assembly section analyzes whether Democrats can maintain or regain a two-thirds majority, listing numerous competitive districts shaped by retirements, reapportionment, and strong challengers. Overall, the piece emphasizes tight races, shifting demographics, and the strategic importance of voter registration margins in determining party control of California's legislative bodies.